2021
DOI: 10.1016/j.kint.2021.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin-11, Sparc-related modular calcium binding protein-2, and Pigment epithelium-derived factor are promising non-invasive biomarkers of kidney fibrosis

Abstract: Kidney fibrosis constitutes the shared final pathway of nearly all chronic nephropathies, but biomarkers for the non-invasive assessment of kidney fibrosis are currently not available. To address this, we characterize five candidate biomarkers of kidney fibrosis: Cadherin-11 (CDH11), Sparc-related modular calcium binding protein-2 (SMOC2), Pigment epithelium-derived factor (PEDF), Matrix-Gla protein, and Thrombospondin-2. Gene expression profiles in single-cell and single-nucleus RNA-sequencing (sc/snRNA-seq) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Although they did not specify which CD45 + leukocytes were producing the collagen 1, they concluded that leukocytes contribute 38% to 50% of collagen 1 deposition in renal fibrosis. This is supported by a recent study that reanalyzed the single-cell RNA-Seq data from UUO-injured kidneys ( 47 ): it showed that immune cells, including neutrophils, from injured kidneys express Col1a1 as well as other collagen proteins such as Col5a2 , Col12a1 , and Col15a1 ( 48 ). Our observation that Siglec-F + neutrophils are the major collagen 1–producing leukocytes in the fibrotic kidney is thus consistent with and expands these findings.…”
Section: Discussionmentioning
confidence: 58%
“…Although they did not specify which CD45 + leukocytes were producing the collagen 1, they concluded that leukocytes contribute 38% to 50% of collagen 1 deposition in renal fibrosis. This is supported by a recent study that reanalyzed the single-cell RNA-Seq data from UUO-injured kidneys ( 47 ): it showed that immune cells, including neutrophils, from injured kidneys express Col1a1 as well as other collagen proteins such as Col5a2 , Col12a1 , and Col15a1 ( 48 ). Our observation that Siglec-F + neutrophils are the major collagen 1–producing leukocytes in the fibrotic kidney is thus consistent with and expands these findings.…”
Section: Discussionmentioning
confidence: 58%
“…These enriched pathways again point to cell adhesion and cell signaling as important processes altered in kidney disease, and potentially, pHTN. Studies have shown that EGF and EGF receptor (EGFR) signaling pathways are disrupted in both cardiovascular and renal pathologies, including CKD. , Several cadherins, including E-cadherin, associated here with proteinuria, eGFR < 60, and eGFR < 60 + pHTN (Table S1), have also been studied as potential biomarkers for various types of kidney disease. Utilizing network analysis to identify modules of coordinated protein abundance associated with renal dysfunction and pHTN in SCD thus further implicates ECM and cell signaling proteins and provides specific pathways for future investigation.…”
Section: Discussionmentioning
confidence: 99%
“… [43] , [44] , [45] SMOC2 has been shown to play an important role in renal fibrosis and has been suggested as a potential biomarker. 46 , 47 Whole-body Smoc2 ablation in mice ameliorated diet-induced obesity, hepatic steatosis, and fibrosis. 48 The study also showed elevated SMOC2 mRNA and protein levels in human steatotic liver biopsies and proposed a fibrogenic role for hepatocyte SMOC2 through direct intracellular interaction with TGF-β1.…”
Section: Discussionmentioning
confidence: 99%